Development of a Culture-Based Proactive Coping Intervention Model Using the Balinese Tri Hita Karana Mechanism to Reduce Depression Among Older Adults - I Wayan Suardana; I Ketut Sudiantar; I Ketut Gama; Agus Sri Lestari (Media of Health Research, 2026)
Background: Depression among older adults remains a significant public health concern in Bali, with prevalence reaching 5.1% in 2018, and particularly high rates in Klungkung Regency (51.2% in men and 48.3% in women). Despite the strong cultural roots of Tri Hita Karana in Balinese society, its potential as a proactive coping mechanism to reduce depression has not been systematically investigated. Methods: This quantitative study used a cross-sectional descriptive design and recruited 246 older adults through random sampling from Posyandu for older adults in Klungkung Regency. Data were analyzed using univariate and bivariate (Pearson correlation) analysis at a 95% confidence level. Results: Most respondents were female (54.9%), had an elementary school education (46.7%), worked as farmers (28.5%), and were married (62.2%). The majority demonstrated good overall Tri Hita Karana-based proactive coping (65.4%), while 78.9% showed no depression, and 21.1% had moderate depression. Parhyangan, Palemahan, and Pawongan coping were all significantly and negatively associated with depression (r = −0.300, −0.249, −0.230, respectively; all p < 0.05), with Parhyangan showing the strongest relationship. Overall, Tri Hita Karana-based proactive coping was significantly associated with lower depression scores (r = −0.291; p < 0.05). Conclusion: This study demonstrates that Balinese culture-based proactive coping grounded in Tri Hita Karana meaningfully reduces depression risk among older adults, supporting the development of culturally tailored intervention modules for older-adult care in Bali.